Simulation study on size and location identification of tumors in liver tissue through eddy current distribution analysis - Zulkarnay, Zakaria; Lee, Pick Yern; Azian Azamimi, Abdullah; Ruzairi, Abdul Rahim, Prof. Dr.; Muhammad Saiful Badri, Mansor; Nor Muzakkir, Nor Ayob (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/